Unlocking the power of play: exploring the beneﬁts of traditional games for adapted sports in people with cerebral palsy: a scoping review - Rahman, Mansoor A.; Kumar, Jagadish (Wydawnictwo Akademii Wychowania Fizycznego im. Polskich Olimpijczyków we Wrocławiu, 2025)
Introduction. Adapted physical education is a viable way to improve physical activity in individuals with cerebral palsy. While there is adequate documentation on adapting western games, low- and middle-income countries may lack these resources. Tradi-tional games deeply ingrained in these nations, can be played informally with minimal equipment. Adapting traditional games can be an eﬀective way to increase activity and participation. This review presents the existing body of knowledge and identiﬁes the beneﬁts of traditional games in the context of adapting traditional games for individuals with cerebral palsy.Methods: Two independent authors performed a systematic search of PubMed, Cochrane, PeDro databases and supplemented by manual searches. The initial search yielded 228 studies, 157 articles were excluded based on titles/abstracts, and 25 were excluded after a full-text review. Finally, a total of 11 studies were included in the review.Results: The review results emphasized the ethnomotor perspectives and the health beneﬁts of traditional games. The included studies were geographically diverse: 54.54% were from Asia, 36.36% from Europe, and 9.09% from the United States.Conclusion: Traditional games have the potential to increase activity and participation. Adapting these games could serve as a cost-eﬀective and culturally relevant approach to improve the health and well-being of individuals with cerebral palsy.
Keywords: health beneﬁts; cerebral palsy; adaptive sports